2017
DOI: 10.1167/iovs.16-20964
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Amblyopia Affects Two Eyes: Fellow Eye Deficits in Amblyopia

Abstract: Unilateral amblyopia is a visual disorder that arises after selective disruption of visual input to one eye during critical periods of development. In the clinic, amblyopia is understood as poor visual acuity in an eye that was deprived of pattern vision early in life. By its nature, however, amblyopia has an adverse effect on the development of a binocular visual system and the interactions between signals from two eyes. Visual functions aside from visual acuity are impacted, and many studies have indicated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
65
2
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 300 publications
1
65
2
8
Order By: Relevance
“…Amblyopia principally affects one eye; nonetheless, the non‐amblyopic eye often has an array of small but measurable deficits of spatial, positional and motion sensitivity . Clinically, high contrast recognition visual acuity is the predominant measure that leads to a diagnosis of amblyopia, based on two or more lines difference in visual acuity measured between eyes.…”
Section: Visual Deficits In Amblyopiamentioning
confidence: 99%
“…Amblyopia principally affects one eye; nonetheless, the non‐amblyopic eye often has an array of small but measurable deficits of spatial, positional and motion sensitivity . Clinically, high contrast recognition visual acuity is the predominant measure that leads to a diagnosis of amblyopia, based on two or more lines difference in visual acuity measured between eyes.…”
Section: Visual Deficits In Amblyopiamentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17] A number of these deficits also extend to the nonamblyopic fellow eye. 8,12,14,[18][19][20][21] Beyond the loss of monocular visual function, amblyopia also impairs binocular vision, in part because visual information from the amblyopic eye is suppressed from conscious awareness when both eyes are viewing. [22][23][24][25][26][27] Suppression can affect large areas of the amblyopic eye visual field 28,29 and may play an important role in the visual deficits experienced by patients with amblyopia.…”
mentioning
confidence: 99%
“…Contrary to clinical dogma, vision in the fellow eye is not entirely normal. 46 Careful psychophysical studies have shown that the fellow eye has reduced optotype 4,47 and Vernier acuity, 48 and perhaps more importantly, greater spatial uncertainty and distortion affecting both foveal and extra-foveal vision. 9,10 Such deficits in spatial vision, affecting both the amblyopic and fellow eyes, may therefore contribute to the binocular visual localization deficit observed in the present study.…”
Section: Optimal Audiovisual Spatial Integration In Amblyopiamentioning
confidence: 99%